Caring Science Education: Measuring Nurses' Caring Behaviors. - Ackerman, Linda (International Journal of Caring Sciences, 2019)
This article focuses on reviewing research and evidence-based practices related to Caring Science educational programs, utilizing Caring Science theory as an intervention to inform and impact the nurses caring behaviors while caring for patients within a healthcare environment. While there are multiple survey tools directed at patient's assessing the caring behaviors based on the patient's perception, there are limited surveys that examine the nurse's perception of their caring behaviors and their personal, professional practice relating to Caring Science or relationship-based care and, the impact on their clinical practice post education intervention. The purpose of this article is to better understand the impact and measurement of nurses' self-perception of caring behaviors following the co-creation of the Caring Science/Heart Science standardized educational series in a large multi-site organization and, patient's perception of being "treated with loving kindness." Advancing the art and science of the nursing staff through deepening their understanding of the theory of human caring, engaging their hearts and minds, deepening their understanding of the theory as the foundation for all professional nursing practices within the organization.